2015
DOI: 10.1002/2014wr015769
|View full text |Cite
|
Sign up to set email alerts
|

The effect of streambed heterogeneity on groundwater-surface water exchange fluxes inferred from temperature time series

Abstract: One-dimensional analytical heat transport equations based on temperature time series data have become popular tools to quantify groundwater-surface water interactions. The influence of nonideal field conditions on the use of these equations has been assessed for nonsinusoidal stream temperature signals, uncertainty in thermal parameters, sensor accuracy and multidimensional flow. Given that streambeds are often highly heterogeneous, the influence of streambed heterogeneity on flux estimates from temperature ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 44 publications
(110 reference statements)
0
55
0
Order By: Relevance
“…The velocity fields of some natural conditions tended to be nonuniform. Analysis of non-vertical flow through heat tracing has been well documented by Lautz (2010), Cuthbert and Mackay (2013), and Irvine et al (2015); however, credible patterns of hyporheic exchange can be generated via these analytical solution even at the scale of a river bank or cross section.…”
Section: Analysis Methods Of Vertical Hyporheic Fluxmentioning
confidence: 99%
“…The velocity fields of some natural conditions tended to be nonuniform. Analysis of non-vertical flow through heat tracing has been well documented by Lautz (2010), Cuthbert and Mackay (2013), and Irvine et al (2015); however, credible patterns of hyporheic exchange can be generated via these analytical solution even at the scale of a river bank or cross section.…”
Section: Analysis Methods Of Vertical Hyporheic Fluxmentioning
confidence: 99%
“…However, the influence of the use of a wider range of K (i.e., harddata in the range of 10 −6 to 10 −1 cm/s) on the RT is also examined as a sensitivity analysis. Following a previous example (Irvine et al ), a simple kriging process and spherical model are selected and the variance of ln( K ) is defined as 0.74. The correlation length in the horizontal direction is 2.0 m. The mean K value of each realization in the HeI case is applied to each of the 20 simulations of the HoI case.…”
Section: Methodsmentioning
confidence: 99%
“…Zhou et al () concluded that the flux of a heterogeneous streambed was one order of magnitude higher than that of a homogeneous streambed. Other researchers (Irvine and Lautz ; Irvine et al ) have also discussed the influence of heterogeneity on the HZ fluxes based on temperature time‐series records. Beyond the effect of heterogeneity, Zlotnik et al () considered the influence of large‐ and small‐scale anisotropy on the HZ fluxes at various depths.…”
Section: Introductionmentioning
confidence: 99%
“…After solving for fluid flow in COMSOL, transient heat flow was simulated in the model volume in a manner that is consistent with assumptions of previous work [e.g., Irvine et al ., , Cuthbert and Mackay , ] utilizing the advection‐diffusion equation in three dimensions: ÎŽnormalTÎŽnormalt=Îșe∇2normalT−qρwcwfalse(ρc)b∇normalT …”
Section: Methodsmentioning
confidence: 99%